2014
DOI: 10.1074/jbc.m112.435156
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Chymase Degrades the Alarmins Heat Shock Protein 70, Biglycan, HMGB1, and Interleukin-33 (IL-33) and Limits Danger-induced Inflammation

Abstract: Background: Mast cell chymase may be both pro-inflammatory and anti-inflammatory during infection and tissue damage. Results: Human and mouse chymases modulate extracellular levels of the alarmins Hsp70, biglycan, HMGB1, and IL-33. Conclusion: Mast cell chymase degrades alarmins and may limit inflammation. Significance: Identifying the physiological chymase substrates is crucial for understanding the role of chymase in immune responses and could aid in drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 65 publications
3
97
0
Order By: Relevance
“…Indeed, MC granules contain a wide range of proteases and mMCP-4, the homolog of the human chymase, has been shown to degrade several alarmins, including IL33, both in vitro and in vivo (34,44). Confirmatory evidences in our model came from reconstitution of Kit W-sh mice with BMMCs from mMCP-4 KO mice: mMCP-4 KO BMMCs were unable to promote mucosal healing after DSS withdrawal, unlike WT BMMCs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Indeed, MC granules contain a wide range of proteases and mMCP-4, the homolog of the human chymase, has been shown to degrade several alarmins, including IL33, both in vitro and in vivo (34,44). Confirmatory evidences in our model came from reconstitution of Kit W-sh mice with BMMCs from mMCP-4 KO mice: mMCP-4 KO BMMCs were unable to promote mucosal healing after DSS withdrawal, unlike WT BMMCs.…”
Section: Discussionsupporting
confidence: 54%
“…5C), suggesting that IL33 is either sequestered or destroyed in the presence of MCs. The second hypothesis fits well with MCs known capacity to degrade HSP70, biglycan, HMGB1, and IL33 through the mouse homolog of the human chymase, mMCP-4 (34).…”
Section: Mast Cell Deficiency Impact On Epithelial Cells Activity Dursupporting
confidence: 52%
“…One possible candidate to carry out this function could be chymase, which was shown to be responsible for IL‐6 degradation mediated by human mast cells 12. On the other hand, studies on murine mast cells did not confirm this finding 36. Instead, it was shown that the tryptase mMCP6 (and not the chymase mMCP4) could cleave IL‐6, and that abrogation of this pathway in dipeptidyl peptidase I‐deficient mice could possibly explain their elevated levels of IL‐6 and improved survival in a model of septic peritonitis 13.…”
Section: Discussionmentioning
confidence: 98%
“…is a recently finding cytokine with lots of functions. IL-33 has been reported as a potent inducer of Th2 immune responses as well as "alarmin" cytokine released from necrotic cells (Arshad et al, 2012;Lopetuso et al, 2012;Roy et al, 2014). Recently, some DOI:http://dx.doi.org/10.7314/APJCP.2014.15.8.3503 Correlations Between Serum IL33 and Tumor Development: a Meta-analysis researches reported that IL-33 is play important role in tumorigenesis and tumor progress (Chen et al, 2013;Jovanovic et al, 2014)Serum IL-33 may be a useful indicator for prognosis of tumor (Sun et al, 2011).…”
Section: Discussionmentioning
confidence: 99%